A study on integrated water resources management of Pamaluru Watershed Project, Kadapa district, Andhra Pradesh - HAREESH, DHARA; NAYAK, R.C.; KIVISHE (Journal of Soil and Water Conservation, 2026)
The Pamaluru area in the Kadapa district of the Indian state of Andhra Pradesh, where the proposed watershed is located, has a total geographical area of 1209 ha. This project was chosen to alleviate the socioeconomic conditions of the local population as well as to conserve and promote both crop lands and cultivable degraded lands in the area. It intends to increase crop production to supply food, fodder, and other biomasses. The amount of rainfall to be made available for all the 52 weeks of the year meant for crop growth in the watershed is estimated at a probability level of 75%. It is advised to grow crops on 351 ha of watershed’s projected cultivable land. According to the state government’s recommendation, an irrigation schedule is developed based on the cropping pattern. The installation of submersible pumps to harvest the groundwater resources in the cropland is suggested for development of the watershed.